Students’ Motivation in Learning English by Using Content Language Integrated Learning (CLIL) Approach in Management class Economic Faculty at Muhammadiyah University - Nevia, Yayah Ikhda (Jurnal Penelitian Ilmu Sosial dan Eksakta, 2024)
Content and Language Integrated Learning (CLIL) refers to a teaching and learning process where students learn other subjects such as physics or geography through a foreign language and also learn a foreign language through content-based subjects. This study was a classroom action research, which aims to  increase students' motivation  in  learning  English  through  the  Content  and  Language  Integrated  Learning (CLIL) approach. Previous research at management class discovered that most the first -grade students were passive and needed more motivation to learn English.  This research was conducted in collaboration with the English teacher who served as the study's observer. This study was divided into two cycles, each with two meetings. It was carried out over seven meetings, including a preliminary study and completing a questionnaire. According to observations, student participation in cycle 1 was 48.28% at the first meeting and 65.52% at the second. Meanwhile, student participation in Cycle 2 has increased. Student participation was 75.86% at the first meeting and 86.2% at the second. These findings indicate that student participation has met the study's success criteria, namely, 75% or more of the total number of students increased. In the first meeting, the student's participation was 75,86%, and in the second meeting was 86,2%. This result indicated that the student's participation had achieved this research's success criteria, more than 75% or more of the total number of students.